Issues of Reservation and Affirmative Action for Minorities in Nepal: An Anthropological Review - Prasai, Dilli R. (Himalayan Journal of Sociology and Anthropology, 2017)
There are mainly six types of minorities in Nepal. It is categorized not only numerically but also on the basis of access in ruling process of the state. The caste, gender, region, religion, inhabitation and language, which have no access in the governing process is also categorized under minorities. Dalit is a caste which are being discriminated as an untouchable group since the beginning of Muluki Ain of Nepal. Women are marginalized politically, socially and financially and treated as the weak individuals. Western and far western regions of the country are very much backward in terms of infrastructure development, human resource, education and in all sectors in comparison to other regions of the country. All religions are discriminated by the state excluding Hindu religion. Madhesi is another part of discrimination by inhabitation of the country. We can take some affirmative action towards enhancement of minorities. Provision of proportional representation, reservation, different acts and statutes, secular state including the interim constitution, made by state is also an example of affirmative action towards promotion of minorities. Himalayan Journal of Sociology & Anthropology - Vol. VII (2016), Page: 1-12